2018
DOI: 10.18203/2394-6040.ijcmph20183558
|View full text |Cite
|
Sign up to set email alerts
|

Improving hand hygiene compliance among healthcare workers in intensive care unit: an interventional study

Abstract: Background: Hand hygiene (HH) is one of the most important measures to prevent healthcare-associated infections. The objective of the study was to assess the effectiveness of the augmented multi-interventional approaches on HH compliance rate among intensive care unit (ICU) healthcare workers (HCWs) of Farwaniya Hospital, Kuwait.Methods: An interventional study was conducted in four phases throughout eight months among adult ICU HCWs. First; HCWs, HH compliance rates and alcohol-based hand rub consumption rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
6
2
Order By: Relevance
“…The rationale behind this observation could be the increased concern of HCWs for HH when performing an aseptic procedure, compared to other moments which don't involve any invasive procedures, although all the 5 WHO moments should be considered equally important. This finding is also in contrast to few other studies where HH compliance rate was higher for other WHO moments; for example, increased compliance for after moments was documented by A.S. Sastry et al, A.M. Laskar et al, Rodriguez et al, and Naglaa et al; whereas increased compliance for before moments was reported by Lohiya et al 15,17,24,26,27 Month-wise comparison of HHTAR and device associated infection (DAI) rates was depicted in Figure 2. A good HH compliance directly reflects in reduction in HAIs and eventually results in effective healthcare system.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The rationale behind this observation could be the increased concern of HCWs for HH when performing an aseptic procedure, compared to other moments which don't involve any invasive procedures, although all the 5 WHO moments should be considered equally important. This finding is also in contrast to few other studies where HH compliance rate was higher for other WHO moments; for example, increased compliance for after moments was documented by A.S. Sastry et al, A.M. Laskar et al, Rodriguez et al, and Naglaa et al; whereas increased compliance for before moments was reported by Lohiya et al 15,17,24,26,27 Month-wise comparison of HHTAR and device associated infection (DAI) rates was depicted in Figure 2. A good HH compliance directly reflects in reduction in HAIs and eventually results in effective healthcare system.…”
Section: Discussioncontrasting
confidence: 73%
“…A previous large-scale study conducted for one year at the same facility in 14 different non-COVID critical care areas documented HHTAR, HHCAR and HHPAR of 66.8%, 45.5% and 21.2% respectively. 15 In concordance, there are several studies on HH auditing in non-COVID ICUs published elsewhere which documented HH compliance ranging from 14% by Bhattacharya et al, 25 56.0% by Lohiya et al, 17 66.0% by Rodriguez et al 26 to 73.17% by Naglaa et al 27 We have made an effort to analyze HHTAR (complete and partial) in this study, even though WHO does not recommend to monitor partial compliance. This attempt was taken in order to encourage the HCWs in a hope that their partial HH adherence will be converted to complete adherence in the subsequent audits.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In the study, the use of povidone-iodine or alcohol instead of chlorhexidine is thought to stem from their low cost and availability. [36][37][38][39][40] In a study on the knowledge levels of nurses about CCRBI in Poland, 50% of nurses (n = 301) reported that chlorhexidine should be used in CVC dressings. [17] Also, the rate of correct responses by the nurses to the question "Which handwashing method do you use while giving care to a patient with CVC?"…”
Section: Discussionmentioning
confidence: 99%
“…[11,14,18] This is stated to be due to seeing hand washing less important than other procedures, lack of time due to heavy workload, and inadequate training in this issue. [40,41] In a study conducted to determine the handwashing status of nurses working in the hospital, 92.9% of the nurses were found to be not trained in handwashing after graduation, and the most important reason affecting handwashing was the insufficient number of nurses per patient. [19] The planning of nurses in health institutions in our country is conducted according to the "Ministry of Health Provincial Organization, Bed and Staff Standards Regulations for Inpatient Treatment Institutions".…”
Section: Discussionmentioning
confidence: 99%